(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to analyze the influence of transformational leadership style, work environment, job satisfaction and work discipline on the performance of employees of PT Indomarco Prismatama Bogor 1 Branch. The analytical method s in this research are descriptive analysis and inferential analysis. Data analysis from several tests, namely ins trument testing, classical assumption testing, model feasibility testing, multiple liners analysis and t - hypothesis testing, was conducted. The subjects of this research were employees of PT Indomarco Pismatama Bogor 1 Branch, with a total of 119 employees using data collection methods via questionnaires. The results of the regression analysis in this research shows that there is a positive and significant influence on performance, which is shown in the coefficient table in the regression equation models. The results of the ANOVA statistical test for the feasibility of the model show significant results, so that the model used has a relationship with the performance variable.